Development of diamond-like carbon films by ECR-CVD - Yang, Hong (2009)
Hydrogenated amorphous carbon (a-C: H)thin films have attracted considerable interest due to their unique properties such as chemical inertness, mechanical hardness and high photoluminescence efficiency at room temperature. Specifically, a-C: H which exhibit diamond-like properties such as mechanical hardness have been successfully applied in various fields such as optical, wear and corrosion resistant coatings.